Mapping drivers of second-generation South Asian American eating behaviors using a novel integration of qualitative and social network analysis methods. Issue 4 (4th July 2022) - Ali, Shahmir H.; Gupta, Srishti; Tariq, Maham; Penikalapati, Rushitha; Vasquez-Lopez, Xilonen; Auer, Sian; Hanif, Channan; Parekh, Niyati; Merdjanoff, Alexis A.; DiClemente, Ralph J.
ABSTRACT: This study explores a novel, mixed qualitative method to deconstruct the diet of second-generation South Asian Americans (SAAs). Online interviews of 32 second-generation SAAs were conducted usingintegrated free-listing and mind-mapping. Ranked free-lists were aggregated to identify salient drivers, while connections made within mind-maps were analyzed using social network analysis (SNA) methods. Overall, 34 distinct drivers and 247 unique connections were identified. Taste, family, and health had the highest adjusted rankings, while health displayed the strongest network centrality. Interventions aimed at second-generation SAA dietary behaviors may benefit from family-based or multi-level interventions, which consider the complex, unique dietary norms identified.